2010
DOI: 10.1089/ten.tec.2008.0693
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Isolate Mesenchymal Stem Cells from Bone Marrow in a Closed System Using a Device Made by Nonwoven Fabric

Abstract: Bone marrow stromal cells (BMSCs) include cells with multidirectional differentiation potential described as mesenchymal stem cells. For clinical use, it is important to develop a way to isolate BMSCs from bone marrow in a closed system without centrifugation. After screening 200 biomaterials, we developed a device containing a nonwoven fabric filter composed of rayon and polyethylene. The filter selectively traps BMSCs among mononuclear cells in bone marrow based on affinity, not cell size. The cells are then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…[11][12][13] MSC and PRP alone or in combination have been used previously to promote bone regeneration. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Sheep have been demonstrated to be appropriate animals in orthopedic research due to their ability to tolerate surgery well and to recover quickly, as reported in our study and in other ones as well. 30,31 The majority of total hip replacement studies in sheep and goat pertain to the bone-cement interface, while the bone-prosthesis interface in non-cemented hip prostheses remains relatively unstudied.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…[11][12][13] MSC and PRP alone or in combination have been used previously to promote bone regeneration. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Sheep have been demonstrated to be appropriate animals in orthopedic research due to their ability to tolerate surgery well and to recover quickly, as reported in our study and in other ones as well. 30,31 The majority of total hip replacement studies in sheep and goat pertain to the bone-cement interface, while the bone-prosthesis interface in non-cemented hip prostheses remains relatively unstudied.…”
supporting
confidence: 80%
“…MSC have been utilized in numerous studies as a source of osteogenic cells for bone repair because the bone‐specific differentiation of MSC has been well‐documented in vitro 11–13. MSC and PRP alone or in combination have been used previously to promote bone regeneration 14–29. Sheep have been demonstrated to be appropriate animals in orthopedic research due to their ability to tolerate surgery well and to recover quickly, as reported in our study and in other ones as well 30, 31.…”
supporting
confidence: 70%
“…Thus, nonwoven filters in general may be suitable for the capture of cells for regenerative medicine. For example, nonwoven filters composed of rayon and polyethylene can be used to isolate bone marrow stem cells from bone marrow aspirates [4].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of these stem cells from total marrow is usually conducted using a sucrose-based density gradient column, which is a time-consuming process. After screening 200 biomaterials, Ito et al (2010) selected rayon-polyethylene nonwoven fabric for the development of a fi lter for the collection of mesenchymal stem cells from bone marrow hematopoietic mononuclear cells. Mesenchymal stem cells adhered tightly to highly hydrophilic and rough surfaces as compared to hydrophobic and smooth surfaces, resulting in a rapid and effi cient method of cell isolation fi ltration.…”
Section: Filtration Materials For Medical Applicationsmentioning
confidence: 99%